2018
DOI: 10.3390/app8050750
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties and Chemical Resistance of New Composites for Oil Pump Impellers

Abstract: In this paper, a new class of high-performance composites and a method of their production based on the carbonization of an elastomeric matrix are proposed. The use of elastomeric matrix makes it possible to manufacture products with complex shapes, while the subsequent carbonization can significantly improve their properties by changing the chemical nature of the elastomeric matrix. Such an approach can reduce the products' machining cost, especially for composites reinforced with super hard fillers such as s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…4,5 SiC is considered as one of the most promising candidate materials for impellers served in the abovementioned extreme conditions, due to its excellent properties including corrosion resistance, wear resistance, oxidation resistance, radiation resistance, thermal shock resistance, low thermal expansion, high thermal conductivity, high creep resistance, and strength retention at elevated temperature. 6,7 However, the high hardness and brittleness of SiC ceramics bring great difficulties to its forming and processing. 8 SiC components are typically produced by the pressure-assisted processing methods such as cold-pressed forming followed by pressureless sintering and hot pressing sintering.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 SiC is considered as one of the most promising candidate materials for impellers served in the abovementioned extreme conditions, due to its excellent properties including corrosion resistance, wear resistance, oxidation resistance, radiation resistance, thermal shock resistance, low thermal expansion, high thermal conductivity, high creep resistance, and strength retention at elevated temperature. 6,7 However, the high hardness and brittleness of SiC ceramics bring great difficulties to its forming and processing. 8 SiC components are typically produced by the pressure-assisted processing methods such as cold-pressed forming followed by pressureless sintering and hot pressing sintering.…”
Section: Introductionmentioning
confidence: 99%
“…The high value of the temperature of the second highest decomposition rate (T2 = 557.4 °C) observed for the o-NBR-grafted silane suggests formation of a carbonaceous residue from o-NBR during the thermal decomposition. The acrylonitrile mers present in the o-NBR macromolecular backbone are considered to be able to trigger carbonization of NBR-based composites [11,12]. Under synthetic air atmosphere the carbonaceous char burns out completely leaving only silica as non-flammable residue (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…It was concluded that the fibre glass/epoxy composite present better stress bearing capacity compared to other metallic materials, except titanium alloys. The production method and use of elastomeric matrix composites has been investigated by Chukov et al [ 23 ] that could be used to manufacture products with complex shapes as pump impellers. Two impeller prototypes were designed, manufactured and analysed.…”
Section: Introductionmentioning
confidence: 99%